Christianity and international law: an introduction - Slotte, Pamela; Haskell, John D. ca. 20./21. Jh. (Law and christianity, 2021)
John D. Haskell & Pamela Slotte / Christianity and international law : an introduction -- Peter Petkoff / The Byzantine Commonwealth and the emerging features of a law of nations in the first millennium -- Tiziana Faitini and Dante Fedele / Christianity and the birth of ambassadorial deontology : some historical notes -- Stefan Stantchev / Formation and refiguration of the canon law on trade with infidels (ca. 1200 - ca. 1600) -- David M. Lantigua / God, sovereignty, and the morality of intervention outside Europe -- Jennifer L. Beard / The significance of Christian charity to international law -- Roland Boer / Hugo Grotius on freedom of the seas and human nature -- Janne E. Nijman / Ius gentium et naturae : the human conscience and early modern international law -- Reut Yael Paz / Legalizing antisemitism? The legacy of savigny's roman(tic) law -- Jedidiah J. Kroncke / Missionary knowledge and the empirical foundation of modern international legal thought -- Andrew Preston / Standards for a righteous and civilized world : religion and America's emergence as a global power -- Udi Greenberg / International Protestantism and its changing religious freedoms -- Linde Lindkvist / Beyond the freedom of worship : the contested meaning of religious freedom in international human rights law and politics, 1945=1967 -- Mark C. Modak-Truran / Process theology and a pluralistic foundation for human rights -- Elena Namli / Christianity and human rights law : Orthodox perspectives -- Nathaniel Berman / Conquest, sacred sites, and "religion" in a time of crisis -- Craig Mousin / Constantine's legacy : preserving empire while undermining international law -- Silas W. Allard / Hopelessly practicing law : asylum seekers, advocates, and hostile jurisdictions -- Akbar Rasulov / The hidden theology of international legal positivism.